Analysis of Dividend Policy and Stock Return in Nairobi Securities Exchange, Kenya - Oluoch, Ondiwa Simon; Aila, Onyango Fredrick (My University, 2022)
Global Securities Exchange witnessed slow performance between 2009 and 2018. Foreign direct investment declined in developed countries and also in Africa. In Kenya, Nairobi Securities Exchange Witnessed Volatile performance during the study period with 2011 and 2015 revealing bear run. During the period of volatility, making investment decisions by investors may have been challenging. Performance indicators such as NSE 20 Share Index, market capitalization, equity turn over, liquidity of stocks all were not stable and witnessed downward trend within the study period. The study sought to analyze the relationship between dividend policy and stock return in Nairobi Securities Exchange. The study is anchored on stock return theories and dividend policy theories .Reviewed literature revealed varied results. Studies reviewed used different methodology and variables arriving at conflicting results. Limited studies reviewed conform to the present study. The study adopted longitudinal research design; the target population was Nairobi Securities Exchange. Secondary data was drawn from Nairobi Securities Exchange. Results revealed that dividend policy significantly influence stock return (R2=0.1882, p=0.024<0.05), consequently, dividend yield has an inverse significant relationship on stock return in Nairobi Securities Exchange, (p=0.007<0.05). Result of this study is useful to policy makers, investors, regulators and finance analyst.
Keywords: Stock return; Investment; Dividend Policy